Global TV : Exporting Television and Culture in the World Market. - Bielby, Denise D. (NYU Press, 2008)
A reporter for the Los Angeles Times once noted that " I Love Lucy is said to be on the air somewhere in the world 24 hours a day." That Lucy's madcap antics can be watched anywhere at any time is thanks to television syndication, a booming global marketplace that imports and exports TV shows. Programs from different countries are packaged, bought, and sold all over the world, under the watch of an industry that is extraordinarily lucrative for major studios and production companies. In Global TV, Denise D. Bielb and C. Lee Harrington seek to understand the machinery of this marketplace, its.